Prefrontal FGF1 Signaling is Required for Accumbal Deep Brain Stimulation Treatment of Addiction - Wan‐Kun Gong; Xue Li; Le Wang; Qian Yang; Alix Tiran‐Cappello; Zhichao Liang; James Samsom; Quanying Liu; He Lin; Christelle Baunez; Fang Liu; Ti‐Fei Yuan (Advanced Science)
Abstract Deep brain stimulation (DBS) has emerged as a prospective treatment for psychiatric disorders; for example, DBS targeting the nucleus accumbens (NAc) abolishes addictive behaviors. However, neither the core pathway nor the cellular mechanisms underlying these therapeutic effects are known. Here, morphine‐induced conditioned place preference (CPP) in mice as an addiction model and NAc‐DBS combined with adeno‐associated virus gene delivery for activity‐dependent tagging, transgenic and chemogenetic manipulation of recruited neuronal networks are used. It is reported that a cortical‐accumbal pathway and local fibroblast growth factor 1 (FGF1) signaling in the medial prefrontal cortex (mPFC) are critical for NAc‐DBS to be effective in altering morphine CPP. It is shown that NAc‐DBS retrogradely activates mPFC neurons projecting to the NAc, and chemogenetic activation/inhibition of these DBS‐activated neuron ensembles in the mPFC reproduces the NAc‐DBS effects on CPP. Sustained therapeutic effects accompany reductions in local FGF1 binding to fibroblast growth factor receptor 1 (FGFR1) in these neurons. Additionally, overexpressing FGF1 in the mPFC‐NAc pathway abolishes the therapeutic effects of NAc‐DBS. These results demonstrate that the mPFC‐NAc pathway forms a top‐down motif to regulate the therapeutic effects of subcortical DBS on addiction. These results support the potential for addiction treatments involving FGF1 signaling and highlight the mPFC as a target for noninvasive brain stimulation.